The Value Clarification Technique Learning Model Improves the Character of Elementary School Students - Berliana Nur Hidayati; Minsih (International Journal of Elementary Education, 2023)
Parents and teachers are facing a decline in the character of several Indonesian children at the elementary school level. In response to this, character education must be encouraged. In the school environment, character education can be taught, one of which is through learning civics education (PKN), with the hope that students can behave appropriately by all the precepts of Pancasila. This study aims to analyze the VCT (Value Clarification Technique) model for improving good character in students after learning PKN. This study uses a quantitative method with pre-test and post-test approaches presented with descriptive analysis. The research design used is Quasi-Experiment: One-Group Pretest-Posttest Design. The subjects of this study were 38 students. Methods of data collection with tests. Data collection instrument with test questions. Data analysis techniques have three stages: data reduction, data presentation, conclusion, and data validation. The research results show an increase of 45% in the excellent character of students who comply with the five Pancasila precepts. VCT can be a learning model considered effective in improving and enhancing student character.